Secondary school teachers psychological status and competencies in e-teaching during Covid-19 - Wong, Kai Yan; Sulaiman, Tajularipin; Ibrahim, Amalina; Kunchi Mohd, Abdul Gaffar; Hassan @ Hussin, Omrah; Wan Jaafar, Wan Marzuki (Elsevier, 2021)
Presents problem/focus of study: The Covid-19 outbreak has had a staggering impact on the global economy, public health and safety, trade and education. In Malaysia, the government implemented the Movement Control Order (MCO) as a preventive measure against Covid-19. In education, the learning process has been transferred to online teaching. However, pandemic pedagogy is making learning into completely online either synchronous or asynchronous. Therefore, the current research aims to determine the secondary school teachers' psychological status, competencies in e-teaching and teachers work motivation as well as determine the relationship between secondary school teachers’ psychological status and competencies in e-teaching during the Covid-19 outbreak. Design/methodology/approach: Current research is a descriptive-correlational quantitative survey to determine teachers' psychological status, e-teaching competencies and working motivation during Movement Control Order (MCO) to contain the Covid-19 pandemic. The study sample consists of 595 secondary school teachers selected via convenient sampling. Quantitative data are collected from an online survey through the questionnaires with demographic, psychological status (stress, anxiety and depression), e-teaching competencies (teaching, monitoring and evaluation) and teaching motivation developed by the researchers were distributed during the MCO period. SPSS 25 is applied, Statistical measures such as Cronbach's alpha, means, percentage and standard deviation were employed to analyze the data to obtain the value of the school teachers' psychological status, e-teaching competencies and teaching motivation. Consequently, a Pearson correlation table was created to show the analysis of the school teachers' psychological status and competencies in e-teaching. Findings: This finding indicated that the teachers' psychological factors in stress, anxiety and depressed are moderate, the teachers' competencies in e-teaching is moderate as well as teachers’ working motivations is also the moderate level. However, the highest mean value was found among the variables, this is revealed that despite the challenges during the Covid-19 outbreak, teachers showed positive and strong motivation in conducting e-teaching. Additionally, the result showed a negative relationship between psychological status and e-teaching competencies (-0.286, p < 0.01), as well as reported a negative relationship between dimension of psychological status and competencies in e-teaching. Limitation & recommendations This study has its limitations: This study is included only Selangor teachers and given that the information obtained from the study was gather from secondary schools, the generalizability might be limited. future research may consider expanding the scope from secondary schools to primary schools' teachers and then to university lecturers. Perhaps the scope is expanding, so more information could be obtaining and help researchers understand the teachers’ competencies in e-teaching, psychological status and work motivation.